Pola Asuh Orang Tua terhadap Kemampuan Bina Diri Anak Disabilitas Intelektual - Sari, Silvia Yustika; Sukmawati, Bhennita; Nurhadiyati, Arifah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This research aims to identify the type of parenting style applied and analyze the impact of parenting styles on children's self-development abilities. The method used is a descriptive qualitative method, where data is collected through interviews, observations, and documentation on parents of students at the Jember State Special School, using a purposive sampling technique. The results of the research show that the parenting style provided by two parents on the self-development abilities of children with intellectual disabilities at the Jember State Special School, namely that parent R applies a combination of authoritarian parenting and democratic parenting. This parenting style can help develop children's self-development abilities well. Meanwhile, M's parents use a permissive parenting style, which can hinder the child's self-development skills. The conclusion of this research shows that parenting styles have an essential role in the self-development abilities of children with intellectual disabilities at the Jember State Special School. Keywords: Parenting Patterns, Self-Development, Intellectual Disabilities